A systematic review and meta-analysis of clinical trials comparing arterolane-piperaquine vs. artemether-lumefantrine for the treatment of uncomplicated falciparum malaria - Mondal, A; Basu, A; Modak, D C; Goswami, R P (Journal of postgraduate medicine, 2025)
Artemisinin combination therapy (ACT) is the World Health Organization (WHO) recommended first-line therapy for falciparum malaria. However, recent concern is ACT resistance. Arterolane-piperaquine is a synthetic alternative to ACT. Our objective was to determine the safety and efficacy of arterolane-piperaquine in comparison with artemether-lumefantrine for the treatment of falciparum malaria. We conducted a systematic review and meta-analysis to determine the safety and efficacy of arterolane maleate and piperaquine phosphate for the treatment of uncomplicated falciparum malaria. We searched PubMed/MEDLINE, Cochrane Library, Google Scholar, Clinical Trials.gov and MedRxiv. Search results were screened by title, abstract, and full text before inclusion into the study. Meta-analysis of risk difference between arterolane-piperaquine and artemether-lumefantrine in regard to safety and efficacy was done using a random effects model. Four randomized controlled trials (RCTs) were included. One RCT had a high risk of bias, while the other three studies had a low risk of bias. The 28-day polymerase chain reaction (PCR) corrected risk difference between the artemether-lumefantrine and arterolane-piperaquine was 0 (95% confidence interval -0.02 to 0.02), whereas the PCR uncorrected risk difference was 0.11 (95% confidence interval -0.06 to 0.27). On 42-day follow-up, the PCR uncorrected risk difference was 0.17 (95% confidence interval -0.05 to 0.38), while the PCR-corrected risk difference was 0.01 (95% confidence interval -0.01 to 0.03). Adverse effect profile was similar with risk difference of at least one adverse effect being -0.01 (95% confidence interval -0.02 to 0.00). The commonly reported adverse effects of arterolane-piperaquine were vomiting, anemia, and pain abdomen. Our study shows that arterolane-piperaquine is non-inferior to artemether-lumefantrine for the treatment of uncomplicated falciparum malaria.